Peningkatan Kapasitas Usaha Produk Olahan Bonggol Pisang melalui Pendampingan Inkubator Bisnis - Wijayanti, Reni; Adfani, Mochamad Diva; Valentina, Chrysta; Siregar, Izza Nur Lathifa; Rahayu, Katharina (Setia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2023)
Indonesia is an agrarian country with a large agricultural resource base, including Indramayu with its vast agricultural land resources and its famous banana cultivation, which is widely spread in the Karangampel area. A company in Indramayu has developed a processed food product called Bongsang (banana trunk) that offers a solution to the problem of banana trunk waste by processing it into a product with economic value. Research also shows that banana trunks contain nutrients and vitamins, making them a healthy and multifunctional product.To improve business capacity, the Bongsang team partnered with a business incubator. The incubator plays an important role in providing training, mentoring, facilitating product development, and access to financial institutions and marketing. The incubation process for Bongsang products lasted for four months and consisted of mentoring and business matching activities. The mentoring provided included main mentoring, legality, production, and marketing. This innovative solution to banana trunk waste processing will become a high-value product and also has the potential to improve the economic situation in the region.